1989
DOI: 10.2307/2328774
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure Decisions by Firms and the Competition for Price Efficiency

Abstract: This paper develops a model of the relationship between investment decisions by firms and the efficiency of the market prices of their securities. It is shown that more efficient security prices can lead to more efficient investment decisions. This provides firms with the incentive to increase price efficiency by voluntarily disclosing information about the firm. Disclosure decisions are studied. It is shown that firms may expend more resources on disclosure than is socially optimal. This is in contrast to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
107
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 3 publications
0
107
0
7
Order By: Relevance
“…Some studies have suggested that companies can decrease the cost of capital by supplying more credible information to external users (Choi, 1974;Fishman and Hagerty, 1989;Healy and Palepu, 1993;Verrechia, 1983). However, these relations can not be analyzed if other factors such as the agency costs (Gurbaxani and Whang, 1991) and the cost-benefit relation of disclosed information (Kelly, 1983) are not considered.…”
Section: Hypotheses and Disclosure Indexmentioning
confidence: 99%
“…Some studies have suggested that companies can decrease the cost of capital by supplying more credible information to external users (Choi, 1974;Fishman and Hagerty, 1989;Healy and Palepu, 1993;Verrechia, 1983). However, these relations can not be analyzed if other factors such as the agency costs (Gurbaxani and Whang, 1991) and the cost-benefit relation of disclosed information (Kelly, 1983) are not considered.…”
Section: Hypotheses and Disclosure Indexmentioning
confidence: 99%
“…We follow prior literature in calling this relation the future earnings response coefficient (FERC) or the informativeness of stock price. Studying this association is important because more informative stock prices can lead to more efficient resource allocation (Durnev et al 2003;Fishman and Hagerty 1989). 1 Our study is motivated by recent calls for the permanent elimination of quarterly earnings guidance by the US Chamber of Commerce, the CFA Institute, the Business Roundtable Institute for Corporate Ethics, and The Conference Board (which we collectively call ''the Chamber of Commerce and others'') (CFA Institute 2006;Chamber of Commerce 2007;McCafferty 2007).…”
mentioning
confidence: 99%
“…Concerns about management incentives resulting from quarterly earnings guidance also appear regularly in the business press. 3 1 Fishman and Hagerty (1989) show that the information efficiency of a firm's stock price is linked to the efficiency of its investment and production decisions, suggesting that improved stock price informativeness benefits both the firm and the economy. 2 Interestingly, some companies, including Berkshire Hathaway, Coca-Cola, McDonald's, Pfizer, and The Washington Post Co., have discontinued the practice of forecasting quarterly earnings.…”
mentioning
confidence: 99%
“…30 Fishman and Hagerty (1989) and Dow and Rahi (2002) analyze how the information gathered in the market place affects a firm's investment decisions; Gertner, Gibbons, and Scharfstein (1988) investigate how product-market considerations influence an informed firm's decision to reveal information to the capital market; Poitevin (1989) shows how a financially-constrained entrant, by signaling information about its leverage to the capital market, spurs a "deep-pocket" incumbent to engage in predatory practices. …”
Section: Discussionmentioning
confidence: 99%